The Moderating Role Of Safety Perception On Perceived Justice And Service Recovery Satisfaction Relation - Muhammad, Halirua; Ibrahim Naala, Mohammad Nura (School of Social Sciences, USM, 2017)
Several studies have reported significant link between perceived justice dimensions, and satisfaction service recovery with different impact of the dimensions (procedural, interactional, distributional) on satisfaction service recovery, and some prove similar relationship between the dimensions using different antecedents and variables for example Brand equity, Corporate social responsibility and Switching cost. The present study aims to propose the moderating role of safety perception in the relation between perceived justice and service recovery satisfaction. Data on perceived justice with service recovery satisfaction and safety perception is to be collected through survey from domestic airline passengers in Nigeria. Similarly, safety perception is suggested to play a moderating role between perceived justice (procedural, interactional, distributive) and service recovery satisfaction. The highlights to be provided can assist in addressing the service failure problem confronting domestic airline industry in Nigeria.